2014
DOI: 10.1016/j.cogpsych.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Memory indexing of sequential symptom processing in diagnostic reasoning

Abstract: Explaining symptoms by the most likely cause is a process during which hypotheses are activated and updated in memory. By letting participants learn about causes and symptoms in a spatial array, we could apply eye tracking during diagnostic reasoning to trace the activation level of hypotheses across a sequence of symptoms. Fixation proportions on former locations of possible causes reflected the causal strength of initial symptoms, a bias towards focal hypotheses, and the final diagnosis. Looking-at-nothing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 64 publications
(6 reference statements)
6
43
0
Order By: Relevance
“…We are confident that the retention interval could be extended. Once the integrated representation of cues and locations is stored in long-term memory, it should induce gaze behavior based on reestablished spatial indices whenever it is activated (Jahn & Braatz, 2012). The results also suggest that it might be possible to present more than two reference frames concurrently and, thus, to study decision tasks that involve more than two alternatives.…”
Section: Memory Indexing As An Extension Of Looking At Nothingmentioning
confidence: 94%
“…We are confident that the retention interval could be extended. Once the integrated representation of cues and locations is stored in long-term memory, it should induce gaze behavior based on reestablished spatial indices whenever it is activated (Jahn & Braatz, 2012). The results also suggest that it might be possible to present more than two reference frames concurrently and, thus, to study decision tasks that involve more than two alternatives.…”
Section: Memory Indexing As An Extension Of Looking At Nothingmentioning
confidence: 94%
“…[123][124][125][126][127][128][129][130] Related concepts and antecedents directed at cues, 122,123,131 key features, 132 hypothesis testing [127][128][129]133 and statements made or a situation presented. 126,133,134 The consequence was a formed judgement 125,127,[135][136][137] and attributes included critical thinking, 122,134,136,[138][139][140][141][142][143] reflection, 141 weighing information, 132 flexibility in thinking. 142 There is recognition that human reasoning is error prone.…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
“…For instance, participants who first encode an arrangement of objects and are later asked to recall aspects of that arrangement while looking at a blank screen will spontaneously execute eye movements "to nothing" on the blank screen, which largely correspond to the original object arrangement (e.g., Altman, 2004;Johansson & Johansson, 2014;Spivey & Geng, 2001). Research using such a blank-screen design has demonstrated that eye-movement patterns typical of various decision making strategies remain when decisionrelevant information is removed from the display and the decision is made strictly from memory (Jahn & Braatz, 2014;Renkewitz & Jahn, 2012;Scholz, von Helversen, & Rieskamp, 2015). In addition, compatibility of gaze positions between encoding and retrieval can increase the likelihood of successful remembering (Johansson & Johansson, 2014) and may trigger other associated memories (Platzer, Bröder, & Heck, 2014).…”
Section: Memory and Visually Available Informationmentioning
confidence: 99%